Cost Recovery and Affordability in Small Drinking Water Treatment Plants in Alberta, Canada. Issue 5 (1st May 2016) - Janzen, Aaron; Achari, Gopal; Dore, Mohammed H.I.; Langford, Cooper H.
Abstract : This paper investigates the cost of providing drinking water to municipalities with populations less than 1, 000 in Alberta, Canada, and presents the current unit costs, cost recovery ratios, and affordability for a sample of 25 communities. Unit costs are found to vary considerably with the volume of treated water and the type of source water. Of the 25 communities investigated, only one community recovers the full cost of treating drinking water, while two of the communities recover their portion of the capital costs (i.e., accepting grants as a gift) as well as the marginal costs. Seven of the communities recover the marginal cost of treating drinking water. The authors conclude that water rates designed to cover the marginal cost are possible for small communities if 2% of the median household income is considered an affordable proportion of income to be dedicated to drinking water.